Audit Committee Charter Scope: Determinants and Effects on Audit Committee Effort. Issue 2 (22nd February 2016) - Böhm, Falko; Bollen, Laury H.; Hassink, Harold F.
Abstract : In general, it is either required or recommended that listed firms adopt, periodically update and publicly disclose a written charter for their audit committee. The ostensible purpose of audit committee charters is to inform the investing public about the role and responsibilities of the audit committee of a given firm and to provide authority, direction and discipline for audit committee members. However, evidence has indicated that the audit committee charters of different firms are boilerplate copies of each other and that firms deliberately decouple actual committee practices from the content of their charters, perversely in those institutional settings characterized by a stringent disclosure regime. This paper, on the other hand, provides evidence for a significant relation between the scope of responsibilities set forth in audit committee charters of large firms and measures of actual committee activity in institutional settings characterized by stringent disclosure regimes, and an absence thereof in voluntary disclosure settings.